Tafsir Hermeneutika Nasr Hamid Abu Zayd - Fatkul Chodir (LP3M STITNU AL HIKMAH MOJOKERTO, 2019)
This study examines the idea of hermeneutics the interpretation of Nasr Hamid Abu Zayd as an update to the theory of the well-established scholars. This article aims to uncover the extent to which the idea of Nasr Hamid Abu Zayd was able to be a solution to the scatecal of textual interpretation of medieval scholars with the basis of the theory of constexstuals based on the theories of hermeneutics. The collection of data is conducted by examining the writings of Nasr Hamid Abu Zayd His work relating to the themes of Tafseer and hermeneutics. The results of the analysis found that according to Nasr Hamid Abu Zayd, the divine Kalam needed to adapt, and become human, because God wanted to communicate to mankind. If God speaks in the language of God, Man will in no way understand. So, in his view, the Qur'an is a human language as a result of cultural products. Nasr Hamid Abu Zayd does not agree on the interpretation of the majority of the more dominant exegetes with Islamic metaphysical charges. In his view, such a methodology will not give birth to a scientific stance, because the belief in the metaphysical form of the text (Qur'an) will eliminate efforts of scientific understanding of the phenomenon of text. From this point, Nasr Hamid Abu Zayd initiated the study of the Qur'anic text by placing the Qur'anic text as a cultural product (Muntaj Al-Tsaqafat), as well as producing culture (Muntij Li Al-tsaqafat). This study can at least enrich the research materials of researchers and academics in the field of interpretation of hermeneutics